Analisis Strategi Keberlanjutan pada Perusahaan Unilever - Baginda, Ariq Naufal; Fauzi, Achmad; Yulius Caesar, Leo Andri; Iswanto Putra, Anthony Widjaja; Aadilah Atriliano, Rafi; Larasati, Saskia; Nur Utami, Salma (Dinasti Review Publisher, 2024)
In this research, we will discuss a case study analysis of the implementation of sustainability strategies in Unilever. As a